2019
DOI: 10.1111/eve.13197
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic injury to the parotid salivary gland or duct and the subsequent development of ipsilateral severe peripheral dental caries in two horses

Abstract: This report describes two cases of unilateral traumatic injury to the parotid salivary gland or duct and the subsequent development of severe ipsilateral peripheral dental caries. Ultrasonographic examination of the parotid salivary gland and duct was indicative of parotid glandular atrophy in one case and demonstrated parotid duct obstruction in the second case. To the authors' knowledge, the effects of the loss of function of the parotid salivary gland on the horse's dentition has not been documented and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…5,12,13 There were a small number of cases where horses did deteriorate following the change to a non-cereal hay; however, two of these cases were likely due to the difficulties of assessing the peripheral caries from a single image (see Figure 3), where feed, image quality or lighting made it difficult to accurately assess the peripheral caries. The fact that some did not improve or even deteriorated also likely indicates the multifactorial nature of the condition with other factors such as water source, access to pasture, other dietary factors or concurrent dental or oral pathology 1,8,14 likely also contributing to the condition in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,12,13 There were a small number of cases where horses did deteriorate following the change to a non-cereal hay; however, two of these cases were likely due to the difficulties of assessing the peripheral caries from a single image (see Figure 3), where feed, image quality or lighting made it difficult to accurately assess the peripheral caries. The fact that some did not improve or even deteriorated also likely indicates the multifactorial nature of the condition with other factors such as water source, access to pasture, other dietary factors or concurrent dental or oral pathology 1,8,14 likely also contributing to the condition in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Equine peripheral caries is well known to affect the molars more commonly, and more severely than the premolars, 1,3,15,16 so more subtle changes may be more difficult to grade. This is likely due to the protective effect of the saliva bathing the premolars 3,14 due to the location of the opening of the parotid salivary duct and may also indicate variability in saliva composition as a reason for the variability in improvements in the premolar teeth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest salivary glands communicate with the rostral aspect of the oral cavity (the parotid duct drain at the level of the maxillary Triadan 08 teeth, mandibular salivary ducts under the tongue rostral to the Triadan 06 teeth), so it may be that the buffering capacity of saliva is higher in the rostral area of the mouth. Jackson et al (2019) described two cases of unilateral traumatic injury of the parotid duct and parotid salivary gland, where the horses subsequently developed a much higher grade of caries on the arcades where there was trauma to the gland/duct. Two studies have found that gross examination of equine peripheral caries underestimates the severity of the disease, compared to the histopathological findings (Borkent, Smith, & Dixon 2020;Erridge et al, 2012).…”
Section: Introductionmentioning
confidence: 99%